Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." – Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Strange encounters: embodied others in post-coloniality - Ahmed, Sara (Routledge, 2000)
"Examining the relationship between strangers, embodiment and community, Strange Encounters challenges the assumptions that the stranger is simply anybody we do not recognize and instead proposes that he or she is socially constructed as somebody we already know. Using feminist and postcolonial theory this book examines the impact of multiculturalism and globalization on embodiment and community whilst considering the ethical and political implication of its critique for post-colonial feminism. A diverse range of texts are analyzed which produce the figure of 'the stranger', showing that it has alternatively been expelled as the origin of danger - such as in neighbourhood watch, or celebrated as the origin of difference - as in multiculturalism. The author argues that both of these standpoints are problematic as they involve 'stranger fetishism'; they assume that the stranger 'has a life of its own'". – Site de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme décolonial; histoire et politique; lit4700; philosophie; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; études culturelles

Phénoménologie queer: orientations, objets et autres - Ahmed, Sara (Éditions de la rue Dorion, 2022)
En se concentrant sur l’aspect « orientation » de l’« orientation sexuelle », Sara Ahmed examine ce que signifie pour les corps le fait d’être situés dans l’espace et le temps. Les corps prennent forme lorsqu’ils se déplacent dans le monde en se dirigeant vers ou loin des objets et des autres. Être « orienté » signifie se sentir chez soi, savoir où l’on se trouve, ou avoir certains objets à portée de main. Les orientations affectent ce qui est proche du corps ou ce qui peut être atteint. Selon Sara Ahmed, une phénoménologie queer révèle comment les relations sociales sont organisées dans l’espace, comment la queeresse perturbe et réordonne ces relations en ne suivant pas les chemins acceptés, et comment une politique de désorientation met à portée de main d’autres objets, ceux qui pourraient, à première vue, sembler dérangeants. Dans cet ouvrage fondateur de la réflexion sur le genre écrit en 2006, Sara Ahmed propose qu’une phénoménologie queer puisse étudier non seulement comment le concept d’orientation est informé par la phénoménologie, mais aussi l’orientation de la phénoménologie elle-même. En développant un modèle queer d’orientation, elle combine des lectures de textes phénoménologiques – de Husserl, Heidegger, Merleau-Ponty et Fanon – avec des idées tirées des études queer, de la théorie féministe, de la théorie critique des races, du marxisme et de la psychanalyse.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; féminisme décolonial; har4600; identités LGBTQIA2+; orientation; philosophie; phénoménologie; premier cycle; queer; ressource en ligne; sciences humaines; soc2014; thématiques; études critiques de la race; études féministes

The cultural politics of emotion - Ahmed, Sara (Edinburgh University Press, 2014)
This is a bold take on the crucial role of emotion in politics. Emotions work to define who we are as well as shape what we do and this is no more powerfully at play than in the world of politics. Ahmed considers how emotions keep us invested in relationships of power, and also shows how this use of emotion could be crucial to feminist and queer political movements. Debates on international terrorism, asylum and migration, as well as reconciliation and reparation are explored through topical case studies. In this textbook the difficult issues are confronted head on. New for this edition: a substantial 15,000-word Afterword on 'Emotions and Their Objects' which provides an original contribution to the burgeoning field of affect studies; a revised Bibliography; and updated throughout.
Keywords: approches et analyses; capitalisme; corps; discipline; féminisme; histoire et politique; militance; philosophie; queer; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; émotions; études culturelles